2015
DOI: 10.1039/c5sm00696a
|View full text |Cite|
|
Sign up to set email alerts
|

Films of bacteria at interfaces: three stages of behaviour

Abstract: Bacterial attachment to a fluid interface can lead to the formation of a film with physicochemical properties that evolve with time. We study the time evolution of interface (micro)mechanics for interfaces between oil and bacterial suspensions by following the motion of colloidal probes trapped by capillarity to determine the interface microrheology. Initially, active bacteria at and near the interface drive superdiffusive motion of the colloidal probes. Over timescales of minutes, the bacteria form a viscoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 82 publications
(168 reference statements)
3
50
0
Order By: Relevance
“…Equation 1 has been used previously to interpret the diffusion of bacteria 16 as well as the diffusion of particles in films with bacteria 35 . In the limit of zero bacterial concentration, D A = 0 and eqn (1) Figure 3 shows the long-time particle diffusivity D eff ( Fig.…”
Section: Diffusivity and Cross-over Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 1 has been used previously to interpret the diffusion of bacteria 16 as well as the diffusion of particles in films with bacteria 35 . In the limit of zero bacterial concentration, D A = 0 and eqn (1) Figure 3 shows the long-time particle diffusivity D eff ( Fig.…”
Section: Diffusivity and Cross-over Timesmentioning
confidence: 99%
“…This non-monotonic dependence of D eff on particle size implies that measures of effective diffusivities 25 , effective temperatures 12,33 , and momentum flux 26,27 intimately depend on the probe size and thus are not universal measures of activity. This has important implications for the common use of colloidal probes in gauging and characterizing the activity of living materials, such as suspensions of bacteria 26,27 , biofilms 34,35 , and the cytoskeletal network inside cells 36 , as well as in understanding transport in these biophysical setting. Despite the ubiquity of passive particles in active environments, the effects of size on particle dynamics in active fluids has yet to be systematically investigated in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Films on passive or living substrates allow pathogens to swim or even swarm in order to colonize a wide variety of surfaces including soil, plant leaves, animal tracts or skin [9][10][11]. Liquid-air interfaces have recently attracted interest because of bioremediation of oil-consuming bacteria at oil spill sites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the dynamics of spherical passive tracers have been extensively studied [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], the motion of asymmetric tracers that possess degrees of freedom beyond simple translation has not been investigated until very recently. Peng et al studied the dynamics of isolated ellipsoids in E. coli suspensions and showed that both the translational and rotational diffusion of ellipsoids are enhanced with increasing bacterial con-centrations [39].…”
Section: Introductionmentioning
confidence: 99%
“…Following their pioneering work, the enhanced diffusion of passive spherical tracers has been reported and systematically studied in different active fluids including suspensions of swimming microorganisms such as prokaryotic cells E. coli [17][18][19][20][21][22]24], Bacillus subtilis [25] and Pseudomonas sp. [26] and eukaryotic cell Chlamydomonas reinhardtii [27,28] as well as synthetic colloidal microswimmers [19]. The motion of passive tracers in active fluids is induced by the fluid flow of microswimmers in the far field and the direct steric interaction between tracers and microswimmers in the near field [21,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%